Application of plastics in livestock production: An overview - RAMACHANDRAN, N; SINGH, R K; RAI, B (The Indian Journal of Animal Sciences, 2021)
Plasticulture refers to use of plastics in agriculture in a scientific manner which not only improves the productivity but also optimizes the input resources. The plastic use in livestock farms is also becoming important, particularly for livestock products, for improving its keeping quality; livestock farm operations like storage of feed, feeding and watering devices; animal identification; milking machines and its tubings; milk cans; semen straws and AI sheaths, etc. Recently, the research work has been initiated for the usefulness of plastics in livestock shelter components like floor, wall partitions, protection panels, etc. under AICRP on PET project with ICAR-CIRG, Makhdoom and ICAR-NRCY, Dirang, Arunachal Pradesh for goats and Yaks, respectively as its animal science components. The main plastic products that are utilized on livestock farms are low density polyethylene (LDPE) and polypropylene (PP). This review paper discusses in brief about the plastic use in various stages of livestock production to marketing of its products.